Persepsi Generasi Z Terhadap Food Waste All You Can Eat Hwaga - Muhamad Radihatul Iqbal; Eryd Saputra; Rosie Oktavia Puspita Rini; Agung Arif Gunawan (Journal of Innovative and Creativity, 2026)
This study aims to analyze Generation Z’s perception of food waste at the All You Can Eat Hwaga Restaurant in Batam City by examining the influence of environmental awareness and attitude on behavioral intention to reduce food waste. The research employed a quantitative approach using a survey method with a Likert-scale questionnaire distributed to 200 Generation Z respondents selected through purposive sampling. Data were analyzed using validity and reliability tests, descriptive analysis, Pearson correlation, and simple linear regression with the aid of SPSS software. The results showed that all instruments were valid and reliable, with a Cronbach’s Alpha value of 0.89. The respondents’ average perception score of 4.12 indicated a high level of awareness and positive attitude toward food waste reduction. The regression analysis revealed that environmental awareness and attitude significantly influenced behavioral intention, with an R² value of 0.68. The study concludes that attitude plays the most dominant role in shaping sustainable behavioral intentions; therefore, increasing awareness should be supported by education and social campaigns to foster more responsible consumption behavior.